Effect of row spacing and nitrogen on ratoonability of early maturing high sugar genotypes of sugarcane (Saccharum spp) hybrids - SINGH, A K; LAL, MENHI; PRASAD, S R (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted for 3 years (2 consecutive plant - ratoon cycles) during spring season of 1999-2000 to 2001–2002, to assess the ratoon ability of 3 sugarcane genotypes (’LG 95056’, ’CoPt 84211’ and ’Col 64’) each at 3 row spacing (75, 60 and 45 CD1) and 3 nitrogen levels (150, 187.5 and 225 kg/ha applied to plant cane). Significantly highest nuolber of Illillable ratoon canes (128 000 /’ha) and cane yield (62.9 tonnes/ha) were recorded at 45 cm spacing followed by 60 ell1 (119 400 /ha and 58.2 tonnes/ha) and 75 em (112300/ha and 55.0 tonnes/ha). Ratoon of sugarcane genotype CoPt. 84211’ yielded significantly higher (65.7 tonnes/ha) than ’Col 64’ (52.5 tonnes/ha) and ’LG 95056’ (57.9 tonnes/ha). The number of millable canes in ratoon and cane yield did not exhibit any significant differences due to varying nitrogen levels in the plant cane. The significant interaction between row spacing and genotypes showed that the highest nun1bcr of millable ratoon canes (141700/ha) occurred with ’Col 64’ followed by ’CoPt.842 11’ at 45 cm row spacing, however, highest cane yield (69.2 tonnes/ha) was recorded by ’CoPt. 84211’ at this spacing. The ratoon performance index was estiD1ated to be highest at 45 cm spacing for the genotypes Col 64 and CoPt. 84212 (87.1). The quality parameters did not undergo significant variation due to different treatments and sugar productivity remained a function of sugarcane yield.